The Hidden Prevalence of Male Sexual Assault During War. Observations on Blunt Trauma to the Male Genitals - Carlson, Eric Stener (The British journal of criminology, 2006)
The article presents the author's observation on the prevalence of male sexual assault during war. The International Criminal Tribunal for the Former Yugoslavia investigated sexual assault in the mid-1990s. The male prisoners were sexually assaulted by forced fellatio, masturbation, mutilation of the genitals and insertion of objects into the anus. Sexual torture is widely used to break down the identity of political prisoners. In must cases of sexual assault, the victim is reluctant to admit that he or she was abused. Therefore, it is important to understand the psychodynamics of this trauma